Venous Thromboembolism Prophylaxis in Orthopaedic Trauma Patients: A Survey of OTA Member Practice Patterns and OTA Expert Panel Recommendations. Issue 10 (October 2015) - Sagi, H. Claude; Ahn, Jaimo; Ciesla, David; Collinge, Cory; Molina, Cesar; Obremskey, William T.; Guillamondegui, Oscar
Abstract : Objectives: First, to provide the readership with a summation of the current practice patterns of North American orthopaedic surgeons for venous thromboembolism prophylaxis after musculoskeletal trauma. Second, to establish a set of guidelines and recommendations based on the most current and best available evidence for venous thromboembolism (VTE) prophylaxis after musculoskeletal trauma. Methods: A 24 item questionnaire titled "OTA VTE Prophylaxis Survey" was sent to active members of the Orthopaedic Trauma Association. PubMed and OVID/MEDLINE were used to search the current published literature regarding VTE prophylaxis in trauma patients using the following search terms: deep venous thrombosis, DVT, pulmonary embolism, PE, venous thromboembolism, VTE, prophylaxis, trauma, fracture, pneumatic compression device, PCD, sequential compression device, SCD, screening, ultrasound, duplex, ultrasonography, DUS, venography, magnetic resonance venography, MRV, inferior vena cava, IVC, filter, and IVCF. Each recommendation was graded using articles that were considered by the subcommittee as "the best available evidence" using the grading system adopted and endorsed by the American Academy of Orthopedic Surgeons' Evidenced Based Quality and Value committee. Results: Overall, 185 of 1545 members completed the online survey. The range and variety of prophylaxis and screening methods used among orthopaedic trauma surgeons in North America is large, with a number of agents or methods for which no literature exists to support their use in musculoskeletal trauma. A set of recommendations and guidelines were constructed based on the results of the literature analysis and graded according to guidelines mentioned above. Conclusions: Due to the wide variability in practice patterns, poor scientific support for various therapeutic regimens and important medical–legal implications highlighted by the survey, a standardized set of guidelines and recommendations for VTE prophylaxis after musculoskeletal trauma will be critical in helping to improve patient care and minimize surgeons' exposure to potentially litigious activity. Level of Evidence: Therapeutic Level V. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.